The PERAN KELOMPOK GENERASI BERENCANA DALAM PENCEGAHAN PERKAWINAN USIA ANAK DI KECAMATAN SINTANG PADA DINAS KELUARGA BERENCANA PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN SINTANG - Pether Sobian (Universitas Kapuas Sintang, 2025)
Abstract: The main topic of discussion is the Role of the Planning Generation Group in Preventing Child Marriage in Sintang District at the Family Planning Service, Women's Empowerment and Child Protection, Sintang Regency, wants to know, and describe the Role of the Planning Generation Group in Preventing Child Marriage in the Sintang District. This research method uses a qualitative descriptive research method. The subjects in this research are: 1). Head of the Family Planning Service for Women's Empowerment and Child Protection, Sintang Regency. 2). Head of the Apparatus and General Affairs Subdivision of the Family Planning Service for Women's Empowerment and Child Protection, Sintang Regency. 3). Planning Generation Group Personnel in Preventing Child Marriage in Sintang District 4). Community Elements in Sintang District. The data collection techniques are interviews, observations and documentation studies with data analysis using qualitative data analysis methods. The results of this research show that: The service mechanism; The service mechanism is instructed by the head of the department, passed on to the Head of Subdivision and Family Resilience Group, because GenRe is also under the Head of Youth Resilience Section down to GenRe at the Sintang Regency Family Planning, Women's Empowerment and Child Protection Service. Aspects of program outreach; through social media, such as Instagram, GenRe links and in conjunction with various activities initiated by the Sintang Regency Family Planning, Women's Empowerment and Child Protection Service. Implementation of activities; Implemented in high schools, sub-districts and villages in Sintang Regency where good communication and coordination had previously been carried out. Evaluation of activities; Evaluate the effectiveness of socialization and aspects of program implementation, namely the achievements of activities compared to the program. Achievement of the program in activities. The conclusion is that the role of the Planning Generation Group in preventing child marriage in Sintang District at the Sintang Regency Women's Empowerment and Child Protection Family Planning Service has been running well according to the available budget. Suggestion: The aspect of socialization and implementation needs to be done more massively. Keywords: Roles, Groups, Generations, Planning, Prevention, Marriage, Age, Child